2014
DOI: 10.4103/2230-8210.145075
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pubertal growth and factors influencing it: Can we increase pubertal growth?

Abstract: Puberty is a period of development characterized by partially concurrent changes which includes growth acceleration, alteration in body composition and appearance of secondary sex characteristics. Puberty is characterized by an acceleration and then deceleration in skeletal growth. The initiation, duration and amount of growth vary considerably during the growth spurt. Pubertal growth and biological maturation are dynamic processes regulated by a variety of genetic and environmental factors. Changes in skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 111 publications
4
112
0
3
Order By: Relevance
“…IGF‐I plays a fundamental role in the regulation of growth in height . In our analyses, height had modest positive associations with IGF‐I and IGFBP‐3, and a marked inverse association with IGFBP‐1.…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐I plays a fundamental role in the regulation of growth in height . In our analyses, height had modest positive associations with IGF‐I and IGFBP‐3, and a marked inverse association with IGFBP‐1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to compensatory growth, it is possible that growth spurts are regulated through hormonal mechanisms such as the pubertal growth spurt (Soliman et al 2014), although very little is known about this mechanism in reptiles (Ball & Wade 2013). While no studies have been conducted regarding this phenomenon in sea turtles, Lance et al (2015) found a rise in testosterone levels associated with a growth spurt in male alligators Alligator mississippiensis.…”
Section: Discussionmentioning
confidence: 99%
“…compensatory growth) (Bjorndal et al 2003). Growth spurts may also occur in response to hormonal changes such as those associated with puberty (Soliman et al 2014), although little is known about this mechanism in reptiles (Ball & Wade 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the growth curves, the incompatibility of healthy adolescents’ height/weight growth in comparison with the average in their peers may evoke the concern of parents (Rogol & Hayden, 2014). It is important for some parents to have the adult height of their children in pre-/early adolescence predicted by experts and, if necessary, they should try to increase their height (Carel, 2004; Soliman, De Sanctis, Elalaily, & Bedair, 2014). …”
Section: Introductionmentioning
confidence: 99%